Network Pharmacology and Bioinformatics Analyses Identify Intersection Genes of Vitamin D3 and COVID-19 as Potential Therapeutic Targets - Wang, Shanglin; Gao, Huayu; Wang, Xiaoru; Ma, Xiaoli; Zhang, Lulu; Xing, Yuanxin; Jia, Yanfei; Wang, Yunshan (Frontiers in Pharmacology, 2022)
Purpose: The persistent pandemic of coronavirus disease 2019 (COVID-19), the discovery of gastrointestinal transmission routes and the possible susceptibility of cancer patients to COVID-19 have forced us to search for effective pathways against STAD/COVID-19. Vitamin D3 (VD3) is a steroid hormone with antiviral, anti-inflammatory and immunomodulatory properties. This study aimed to evaluate the possible functional role and potential mechanisms of action of VD3 as an anti-COVID-19 and anti-gastric cancer. Methods: Clinicopathological analysis, enrichment analysis and protein interaction analysis using bioinformatics and network pharmacology methods. Validate the binding activity of VD3 to core pharmacological targets and viral crystal structures using molecular docking. Results: We revealed the clinical characteristics of STAD/COVID-19 patients. We also revealed that VD3 may be anti-STAD/COVID-19 through antiviral, anti-inflammatory, and immunomodulatory pathways. we also identified five core pharmacological targets of VD3 in anti-STAD/COVID-19 and demonstrated the binding activity by molecular docking. Conclusions: This study reveals for the first time that VD3 may act on disease targets such as IL-8 and GM-CSF through inflammatory and viral related signaling pathways and biological functions for the therapy of STAD/COVID-19. This may provide a new idea for the use of VD3 in the treatment of STAD/COVID-19.